A thermoresponsive nanorattle containing two different catalysts for controllable one-pot tandem catalysis. (30th January 2018) - Niu, Chengrong; Hu, Jie; Li, Yinfeng; Leng, Jinghang; Li, Songjun
Abstract: In the present work, a thermoresponsive nanorattle with a Ag nanoparticle (NP) core (one catalyst in the nanorattle), and a poly(N-isopropylacrylamide) shell was developed. An imidazole group was grafted on the polymer shell by copolymerization as the other catalyst. Owing to the catalytic activities of the imidazole group and Ag NP with regards to hydrolysis and reduction, respectively, this nanorattle exhibited tandem-reaction catalytic abilities. In addition, because of the shrinkage of the poly(N-isopropylacrylamide) shell at high temperatures, the tandem reaction could be controlled to stop at the first reaction step. That is to say, only the hydrolysis reaction was catalyzed by the imidazole group being grafted on the surface of the shell. The reduction step in the tandem reaction catalyzed by the Ag particle, however, was switched off by the shrinkage of the poly(N-isopropylacrylamide) shell. This protocol opens up an opportunity to develop controllable catalysts for complicated chemical processes.